Implementation of the Magic Fingers Extracurricular Program as a Stimulation for Early Numeracy Skills of Children Aged 5–6 Years at TK Negeri Pembina Kepanjen - Sovi Nuravida Rahayu Putri; Ajeng Putri Pratiwi (Darul Yasin Al Sys, 2026)
Early numeracy competence is a fundamental component of young children’s cognitive development and provides an essential foundation for subsequent learning in primary education. However, early counting instruction is often dominated by memorization-based approaches that may be less compatible with children’s developmental characteristics and need for concrete learning experiences. This study aims to describe the implementation of the Magic Fingers extracurricular program as a strategy for stimulating early numeracy competence among children aged 5–6 years and to identify the supporting and inhibiting factors influencing its implementation at TK Negeri Pembina Kepanjen. A qualitative approach with a case study design was employed. Data were collected through observations, interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing. The findings indicate that the Magic Fingers extracurricular program was systematically implemented through planning, implementation, and evaluation stages by using finger formations as concrete learning media to introduce number concepts, addition, and subtraction. The program supported the development of children’s early numeracy competence while also strengthening concentration, self-confidence, and active participation. Its implementation was facilitated by strong collaboration among educators, institutional support, and gradual instructional strategies, whereas variations in children’s characteristics and limited learning media constituted the main challenges. These findings demonstrate that the Magic Fingers method offers a developmentally appropriate and concrete learning strategy for strengthening early numeracy competence in early childhood education. This study contributes practical insights into the implementation of extracurricular numeracy activities that align instructional strategies with young children’s developmental needs.